Link capacity design for shared protection with limited traffic information. Issue 1 (1st March 2013) - Matsumura, Ryutaro; Hasegawa, Haruhisa
Abstract : Link capacity for primary and backup paths in a telecommunication carrier network can be computed if the authors are able to use end‐to‐end traffic volume information between source and destination nodes in a network. However, this information is not easily obtained because traffic measurement puts a heavy load on network equipment, and measuring devices are not installed on all the links in the network. Network carriers must estimate the link capacity under limited traffic information. The authors explain a link capacity design problem for shared protection to work within this limitation. Shared protection is effective for economical network design; however, it requires time‐consuming computation. Therefore the authors propose a faster formulation for shared protection that takes the form of a maximum flow problem. The authors evaluated our formulation in terms of the solution's error and showed the advantage of using shared protection.